Somatostatin does not attenuate intestinal injury in dextran sodium sulphate-induced subacute colitis - J. D. van Bergeijk; M. E. van Meeteren; C. J. A. M. Tak; A. P. M. van Dijk; M. A. C. Meijssen; J. H. P. Wilson; F. J. Zijlstra (Hindawi Limited, 1998)
From several in vitro and in vivo studies involvement of som atostatin (SMS) in intestinal inflammation emerge. Acute colitis induced in rats is attenuated by the long-acting SMS analogue octreotide. We studied the potential beneficial effect of SMS on non-acute experimental colitis. BALB/c mice received either saline, SMS-14 (36 or 120 μg daily) or octreotide (3 μg daily) subcutaneously delivered by implant osmotic pumps. A non-acute colitis was induced by administration of dextran sodium sulphate (DSS) 10% in drinking water during 7 days. DSS evoked a mild, superficial pancolitis, most characterized by mucosal ulceration and submucosal influx of neutrophils. Neither SMS-14 nor octreotide reduced mucosal inflammatory score or macroscopical disease activity, although reduction of intestinal levels of interleukin1 β (IL-1 β), IL-6 and IL-10 during DSS was augmented both by SMS and octreotide. A slight increase of neutrophil influx was seen during SMS administration in animals not exposed to DSS. In conclusion, SMS or its long-acting analogue did not reduce intestinal inflammation in non-acute DSS-induced colitis. According to the cytokine profile observed, SMS-14 and octreotide further diminished the reduction of intestinal macrophage and Th2 lymphocyte activity.